Designing of Gombang Fishing Gear Cod End Modification of Reduction ByCatch in the Village Meskom District Bengkalis Regency Bengkalis of Province Riau - Welly Razali; Nofrizal Nofrizal; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conductedon January 2018 in the village Meskom District Bengkalis Regency Bengkalis and laboratory of fishing gear,Fishery Resources Utilization Department, Faculty ofFisheries and Marine, University of Riau.Thepurpose of this research is todesigning of filter net fishing gear cod end modification of reduction by-catch, so it can know the technology for usingBy-catch Reduction Deviceof filter net fishing gear. The filter net Fishing gear used by fishermen of Meskom in its operation which is the target of catching is shrimp of  Mysis sp(udang pepai), while it caught also the juvennile by-catch. Therefore, to anticipate such a case can be done through modification. The type or technology used to cod endmodification of filter net fishing gear is By-Catch Reduction Device (BRD) and for the type of modification used to modify cod endfilter net fishing gear is square mesh window. Keyword: Modification, filter net fishing gear, By-Catch